Organizaciones que aprenden (2019)
This article addresses the importance in the current context of organizations to learn to learn, in a globalized world and with constant changes that requires the process of knowledge acquisition, management transfor-mation, to be at the forefront, achieve success and be a highly competitive organization in the business reality of the twenty-first century. A theoretical analysis was carried out under a bibliographic design that allowed to define, describe and explain, via deductive inference, the organizations focused on learning to learn, the prevailing thought of the subjects and teams learned in systemic organizations, the change, the complex contexts and the management of uncertainty as potential learning resources, the construction of organizational knowledge and finally the approximate ways to learn and build knowledge. The final reflections by way of conclusion reflect how the continuous creation of organi-zational knowledge is the key to ensuring the evolution of the organization and ensures that the organization changes, transcends and evolves.